The Internet under siege. - Lessig, Lawrence (Foreign Policy)
The Internet was successful because its core resources were not controlled by private owners but were held in a “commons.” This commons brought about the extraordinary innovation that the Internet has seen, and its enclosure will bring about the Internet's demise. The most dramatic restrictions on innovation have come at the hands of copyright holders, and their effect on the Internet has been to transfer control over innovation in distribution from many innovators to a concentrated few. Copyright holders have also gained the ability to protect themselves against innovations that could threaten existing business models. The impact of this kind of control will be felt worldwide. Countries with the most to gain from a free and open platform will lose. Nations in the developing world and nations that do not want to cede control to a private corporation will be among those affected.